Case report: Stem cell-based suicide gene therapy mediated by the herpes simplex virus thymidine kinase gene reduces tumor progression in multifocal glioblastoma - Oraee-Yazdani, Saeed; Akhlaghpasand, Mohammadhosein; Rostami, Fatemeh; Golmohammadi, Maryam; Tavanaei, Roozbeh; Shokri, Gelareh; Hafizi, Maryam; Oraee-Yazdani, Maryam; Zali, Ali-Reza; Soleimani, Masoud (Frontiers in Neurology, 2023)
Introduction The prognosis for glioblastoma multiforme (GBM), a malignant brain tumor, is poor despite recent advancements in treatments. Suicide gene therapy is a therapeutic strategy for cancer that requires a gene to encode a prodrug-activating enzyme which is then transduced into a vector, such as mesenchymal stem cells (MSCs). The vector is then injected into the tumor tissue and exerts its antitumor effects. Case presentation A 37-year-old man presented to our department with two evident foci of glioblastoma multiforme at the left frontal and left parietal lobes. The patient received an injection of bone marrow-derived MSCs delivering the herpes simplex virus thymidine kinase (HSV-tk) gene to the frontal focus of the tumor, followed by ganciclovir administration as a prodrug for 14 days. For follow-up, the patient was periodically assessed using magnetic resonance imaging (MRI). The growth and recurrence patterns of the foci were assessed. After the injection on 09 February 2019, the patient's follow-up appointment on 19 December 2019 MRI revealed a recurrence of parietal focus. However, the frontal focus had a slight and unremarkable enhancement. On the last follow-up (18 March 2020), the left frontal focus had no prominent recurrence; however, the size of the left parietal focus increased and extended to the contralateral hemisphere through the corpus callosum. Eventually, the patient passed away on 16 July 2020 (progression-free survival (PFS) = 293 days, overall survival (OS) = 513 days). Conclusion The gliomatous focus (frontal) treated with bone marrow-derived MSCs carrying the HSV-TK gene had a different pattern of growth and recurrence compared with the non-treated one (parietal). Trial registration IRCT20200502047277N2. Registered 10 May 2020—Retrospectively registered, https://eng.irct.ir/trial/48110.